Cross-Database in Deepfake Detection Based on a Convolutional Neural Network and Vision Transformer - Ferreira, Erikson Eler; Andrade, Jefferson Oliveira; Komati, Karin Satie (Anais do Workshop de Visão Computacional (WVC), 2023)
The proliferation of Deepfake techniques has raised concerns due to their potential to generate misleading multimedia content, leading to ethical, social, and political implications. In response to this emerging issue, collaborative efforts between academia and leading technological entities have committed on developing robust detection methods. Initially, Convolutional Neural Networks (CNNs) were prominent, recently proposed methods, which combine features of CNNs with Vision Transformers (ViT) have shown improved performance. This research centers on evaluating the generalization capacity of these advanced models by subjecting them to cross-database tests with different datasets than those used in their training phases. Our analysis reveals that while both models perform well on known datasets, they face challenges related to overfitting when transitioning to new datasets. Consequently, this study underscores the need for further research in Deepfake detection, ensuring its adaptability and effectiveness in diverse scenarios.